Propionic acidemia presenting as encephalopathy, hyper-ammonemia, recurrent pulmonary hemorrhage: A case report - Ramaning Loni; Sachin Tapal; B Anita; Mahesh Kamale; LaxmanLaxman H Bidari (Wolters Kluwer Medknow Publications, 2020)
The metabolic crisis due to inborn error of metabolism can present as an isolated entity or along with the underlying sepsis at any age in children. Here, we present 14 months old boy born of third-degree consanguinity, apparently healthy in the past, admitted with encephalopathy, low GCS, hyperammonemia, and recurrent pulmonary hemorrhage in our hospital, requiring initial resuscitation with stabilization of airway, breathing, circulation, and disability. He required neuroprotective measures including intubation, ventilation with hyperosmolar therapy, and vasoactive drug infusion through the femoral central line for the shock due to metabolic crisis. His urine gas chromatography/mass spectroscopy (MS) for organic acids analysis and blood tandem MS for the plasma amino acids profile, carnitine, and acylcarnitine profile suggested propionic acidaemia, which is rare autosomal recessive disorder and he required dietary modification with metabolic cocktail therapy through a central line with peritoneal dialysis initially for hyperammonemia but subsequently requiring renal replacement therapy to decrease the raised ammonia levels, gradually his sensorium improved, extubated, and sent home with inborn error of metabolism oral cocktail therapy but a few days later, he succumbed to death.